Linking Biodiversity, the Environment and Ecosystem Functioning: Ecological Functions of Dung Beetles Along a Tropical Elevational Gradient - Nunes, Cássio Alencar; Braga, Rodrigo Fagundes; de Moura Resende, Fernando; de Siqueira Neves, Frederico; Figueira, José Eugênio Cortes; Fernandes, G. Wilson (Ecosystems (New York), 2018)
Biodiversity loss and anthropogenic environmental changes are known to impact ecosystem functions and services. However, there are still some uncertainties such as confounding environmental factors other than community attributes that affect ecosystem functioning. Our goal was to understand what factors influence the performance of Scarabaeinae dung beetle functions, testing the hypothesis that both community attributes and environmental variables influence the performance. Toward this aim, we collected dung beetles along an elevational gradient (800–1400 m a.s.l.) in the Espinhaço mountain range (Brazil) and quantified dung beetle functions, that is, dung removal, soil excavation and secondary seed dispersal. We recorded data on environmental factors related to climate, soil and vegetation and evaluated their effects on dung beetle functions. Dung beetle ecological functions declined with elevation and the decrease was more pronounced than richness, indicating that there are other factors involved in functions performance besides diversity of beetles. Indeed, we found that the ecological functions measured were dependent on both dung beetle community attributes and environmental factors. Climate, soil and vegetation influenced dung beetle function performance as much as richness, abundance and body size. Dung beetle functional diversity did not explain any of the functions measured. Our study demonstrates that ecological functions are directly influenced by both community attributes and environmental variables and confirms the link between biodiversity, environment and ecosystem functioning.